Sổ nhật ký nhóm dành cho thúc đẩy viên - Le Thi Tam; Giang Thi Thu Luu; Simelton, Elisabeth; Chi Thi Linh Le; Duong, Minh Tuan; Hoa Dinh Le; Huong Thi Tong (2018)
This group logbook is designed to facilitate the recording of the PSP-group’s observations and monitoring of weather, management, and impacts on farming. Intended for facilitators, this logbook complements or supersedes farmers’ individual logbooks and records a minimum of information. This publication aims to: encourage farmers to document forecasted and observed weather conditions in different seasons; document observations and management of agricultural practices and reflect on agro-advisories developed in the PSP process; document social learning; and document interventions for project monitoring and evaluation purposes.